2015
DOI: 10.1002/ajoc.201500272
|View full text |Cite
|
Sign up to set email alerts
|

Chiral Substituted 3‐Formylfurans from Carbohydrates: An Expedient Route via N‐Bromosuccinimide (NBS)‐Mediated Electrophilic Cyclization

Abstract: Chiral, substituted 3-formylfuransh ave found widespreada pplications as synthetic intermediates and are key structural motifs in av ariety of bioactive natural products. However, methodsf or their preparation are scant. We report herein an efficient and generalr oute to synthesize them from suitably protected 2-iodoenones derived from glycals. The syntheticp rotocol involves Heck coupling between substituted 2-iodoenones and olefinsf ollowed by N-bromosuccinimide (NBS)-mediatede lectrophilicc yclization seque… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 50 publications
0
4
0
Order By: Relevance
“…Das et al. developed an electrophilic cyclization reaction of 2‐alkynylated sugars catalyzed by Au(III), or 2‐enylated sugars mediated N ‐bromosuccinimide (NBS) to form 3‐formylfurans [7c–d] . Hashmi et al.…”
Section: Figurementioning
confidence: 99%
“…Das et al. developed an electrophilic cyclization reaction of 2‐alkynylated sugars catalyzed by Au(III), or 2‐enylated sugars mediated N ‐bromosuccinimide (NBS) to form 3‐formylfurans [7c–d] . Hashmi et al.…”
Section: Figurementioning
confidence: 99%
“…Das and co-authors 95 utilized 2-iodo-enones derived from glycals under palladium-catalyzed Sonogashira and Heck coupling with acetylenes and alkenes for the generation of 2 C -alkynyl and akenyl glycals-enones ( Scheme 46 ). The synthesized 2 C -branched enones were later transformed into highly chirally enriched furans by AuCl 3 and NBS-catalyzed cyclization followed by aromatization reactions.…”
Section: Pd-catalyzed 2 C -Branched Sugar Synthesismentioning
confidence: 99%
“…27 An interesting route to chiral substituted 3-formylfurans 16 from carbohydrates was reported by Das and coworkers. 29 Initially, they prepared a series of 5-iodo-2,3-dihydro-4H-pyran-4-ones 14 from glycals, which in the presence of alkenes under Heck coupling conditions afforded 2alkenylated carbohydrates 15 in 51-80% yields. In a subsequent step, the Heck-coupled products were subjected to electrophilic cyclization promoted by NBS.…”
Section: Scheme 2 N-halo Reagent Induced Endoor Exo-cyclization Modesmentioning
confidence: 99%
“…In addition, a sequential Heck and NBS-promoted cyclization led to the fully substituted chiral 3-formylfuran 17 and furo[3,2-c]pyran 18 (Scheme 5). 29 Scheme 5 Synthesis of chiral substituted 3-formylfurans from 5-iodo-2,3-dihydro-4H-pyran-4-ones NBS has also been used in the synthesis of biologically important dihydrofuropyridinones 20 and furan-3(2H)ones 21. Liang and co-workers 30 reported that 1-alk-2enoylcyclopropane-1-carboxamides 19 were easily cyclized through halonium-induced electrophilic cascades, yielding the corresponding dihydrofuropyridinones 20 or furan-3(2H)-ones 21 in 41-89% yields.…”
Section: Scheme 2 N-halo Reagent Induced Endoor Exo-cyclization Modesmentioning
confidence: 99%